Evaluasi Performa Pertumbuhan Dan Produksi Aksesi Generasi BC2F4 (Inpago 5 dan Inpara 8) terhadap varietas IR 64 pada Lahan Rawa Lebak Dangkal - Rujito Agus Suwignyo; Irmawati Irmawati; Marlin Sefrila; Muhardianto Cahya; Fikri Adriansyah; Habibulloh Habibulloh (Universitas Gadjah Mada, 2026)
The utilization of swamp land in cultivating rice plants has obstacles, especially the presence of abiotic stress, which are submersion in the vegetative phase and drought in the generative phase which impacts productivity. The use of superior varieties that can withstand submersion and drought stress can be a solution in increasing rice productivity in swamp land. This study aims to evaluate the growth and production performance of BC2F4 generation accessions, in shallow swamp land. This study was conducted in Pelabuhan Dalam Village, Pemulutan District, Ogan Ilir Regency, South Sumatra from June to October 2024. This study used a Randomized Block Design using accessions resulting from BC2F4 crosses, including; T1, TR1, T2, TR2, T3, and TR3, as well as Inpago 5 varieties (recipient parents) and IR 64 (popular varieties). The results showed that all BC2F4accessions showed better growth and yield performance compared to Inpago 5. The T3 variety showed the highest productivity at 3.25 tons/ha. In addition, the Pearson correlation showed that productivity was influenced by the variables of the number of tillers (0.58), productive tillers (0.68), and grain weight per panicle (0.89).